Si deus nobis cum… Repetitive Motives of Facades’ Inscriptions on the Buildings in Galicia Region at the Turn of 19th/20th Century - Mysona Byrska, Katarzyna (Vade Nobiscum, tom XXI/2019: Studia z historii gospodarczej, kulturowej i społecznej, 2019)
In the Galicia region during the period of autonomy within the Austro-Hungarian Empire (period between 1866–1914), as a consequence of multiple political and social changes, a huge demographic transformation has occurred, which implemented also a sprouting development of constructions. It is particularly visible in Krakow, but also in few smaller towns in the region. A great number of private building has been constructed (tenant houses, city manors, suburban villas, etc.) as well as public utility buildings. Apart using of new technologies in the construction, in the outside sphere, i.e. buildings decoration, a new tendency has appeared: placing deliberately on the building facades some inscriptions bearing multiple meanings. Some of them are life mottos of the designer or the employer, other are common names given to the houses, or signatures, dates, etc. Interesting is the fact that some of the facades’ inscriptions are repeating the motives put on a building from a previous architectural period, or are copying exactly the same quotation or its variation on the constructions stylistically different, built in different time and located on the territory of the whole Galicia region.